Photothermoelectric Effects and Large Photovoltages in Plasmonic Au Nanowires with Nanogaps - Zolotavin, Pavlo; Evans, Charlotte; Natelson, Douglas (The journal of physical chemistry letters, 2017)
Nanostructured metals subject to local optical interrogation can generate open-circuit photovoltages potentially useful for energy conversion and photodetection. We report a study of the photovoltage as a function of illumination position in single-metal Au nanowires and nanowires with nanogaps formed by electromigration. We use a laser scanning microscope to locally heat the metal nanostructures via excitation of a local plasmon resonance and direct absorption. In nanowires without nanogaps, where charge transport is diffusive, we observe voltage distributions consistent with thermoelectricity, with the local Seebeck coefficient depending on the width of the nanowire. In the nanowires with nanogaps, where charge transport is by tunneling, we observe large photovoltages up to tens of mV, with magnitude, polarization dependence, and spatial localization that follow the plasmon resonance in the nanogap. This is consistent with a model of photocurrent across the nanogap carried by the nonequilibrium, “hot” carriers generated upon plasmon excitation.